THE INFLUENCE OF PARENTAL ATTENTION ON STUDENTS LEARNING DISCIPLINE AT SMP N 7 JAMBI CITY - Rusdayanti, Rusdayanti; Rasimin, Rasimin; Sarman, Freddi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
The aim of this research is to measure the quality of attention of parents of students in class VIII of SMP N 7 Muaro Jambi, to measure the quality of student learning discipline in class VIII of SMP N 7 Muaro Jambi, and to reveal the influence of parental attention on student learning discipline. in class VIII at SMP N 7 Muaro Jambi. This research population was conducted at SMP N 7 Muaro Jambi in class VIII. The subjects of this research were 109 students of SMP N 7 Muaro Jambi, using random sampling techniques. This research data uses descriptive quantitative data. The technique used in this research is by distributing questionnaires to respondents, then analyzing them using the normality test, reliability test, regression test and percentage (%). The results of this research obtained a percentage of 80.58%, this shows the high category, which means that parental attention has a high role for students at SMP Negeri 7 Muaro Jambi. Student learning discipline obtained a percentage result of 87.86%, this shows the high category, which means that student learning discipline has a high role for students at SMP Negeri 7 Muaro Jambi. Based on the results of the research that has been carried out, it is known that there is a quite strong and significant influence between parental attention on student learning discipline at SMP Negeri 7 Muaro Jambi.